Female Innovators at Work Women on Top of Tech - Newnham, Danielle (Apress : Imprint: Apress, 2016)
This book describes the experiences and successes of female innovators and entrepreneurs in the still largely male-dominated tech-world in twenty candid interviews. It highlights the varied life and career stories that lead these women to the top positions in the technology industry that they are in now. Interviewees include CEOs, founders, and inventors from a wide spectrum of tech organizations across sectors as varied as mobile technology, e-commerce, online education, and video games. Interviewer Danielle Newnham, a mobile startup and e-commerce entrepreneur herself as well as an online community organizer, presents the insights, instructive anecdotes, and advice shared with her in the interviews, including stories about raising capital for one's start-up, and about the obstacles these women encountered and how they overcame them. This timely book will be of great interest to anyone working in tech or looking to get into the industry, and more in general: to everyone wanting to learn how they can contribute to leveling the field of occupational opportunity and to strengthening teams and companies through merit and diversity. .